ANALISIS HADIS TENTANG PROSES PEMBELAJARAN YANG MUDAH DAN MENYENANGKAN - Mustofa, Bisri (Jurnal Pendidikan Guru, 2017)
From the fact that human has a nature enormous potential exception learners. If tapped properly it will be very devastatingimpact. Analysis of literature review of this qualitative models using the technique of inductive content analysis. The result is that the Hadith: âMake it easy and do not ye it difficult for. Glad tidings and do not you make it run.â(HR. Bukhari). Is a valid hadith, viewed from various perspectives of the hadith. Hadith message: everything should be easy and enjoyable affair. Particularly relevant as the concept of the learning process. By implementing this hadith is expected to be more meaningful education, to the right goals and objectives and achieve maximum result. The learning process is closely related to the specified learning methods, among examples of the stages of the learning process that can be applied in the educational system by various methods in general, namely preliminary activities, core activities and closing activity. For maximum result should be applied to the concept of the whole process easy and enjoyable. But this has not been done in a comprehensive manner. Bassed on some research result reveal that among the benefits of the learnig process aesy and enjoyable concept is, potential learners can be maximized.